2012
DOI: 10.1183/09031936.00083312
|View full text |Cite
|
Sign up to set email alerts
|

Auto-servoventilation in heart failure with sleep apnoea: a randomised controlled trial

Abstract: We tested the hypotheses that in patients with congestive heart failure (CHF) and sleep disordered breathing (SDB) auto-servoventilation (ASV) improves cardiac function and quality of life.Between March 2007 and September 2009, patients with stable CHF (left ventricular ejection fraction (LVEF) f40%) and SDB (apnoea/hypopnoea index o20 events?h -1 ) were randomised to receive either ASV (BiPAP ASV (Philips Respironics, Murrysville, PA, USA), n537) and optimal medical management, or optimal medical management a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 38 publications
0
51
1
2
Order By: Relevance
“…Thus, ASV, particularly ASV with auto-titrating EPAP, may be a therapeutic option for SDB without the need to distinguish between OSA and CSA. Three randomized controlled trials assessed the effects of ASV on cardiac function in chronic HF patients with coexisting OSA and CSA [55,113,114] . These studies reported significant improvements in cardiac functions, especially reductions in neurohumoral factors.…”
Section: Acute Decompensated Hfmentioning
confidence: 99%
“…Thus, ASV, particularly ASV with auto-titrating EPAP, may be a therapeutic option for SDB without the need to distinguish between OSA and CSA. Three randomized controlled trials assessed the effects of ASV on cardiac function in chronic HF patients with coexisting OSA and CSA [55,113,114] . These studies reported significant improvements in cardiac functions, especially reductions in neurohumoral factors.…”
Section: Acute Decompensated Hfmentioning
confidence: 99%
“…Table 2). 39,[92][93][94][95][96][97][98][99][100][101][102] The majority of studies have been conducted in patients with HF-rEF, but beneficial effects of ASV on respiratory and cardiovascular parameters have also been documented in patients with HF-pEF. 92 Data from a recent meta-analysis showed that ASV significantly improved AHI, left ventricular function and exercise capacity compared with control in patients who had CSA and predominantly HF-rEF.…”
Section: Treatment Of Central Sleep Apnoeamentioning
confidence: 99%
“…As the interest of ASV remains debated in patients with CHF and ''pure'' central sleep apnoea [2], there is no clear evidence of the superiority of ASV over constant positive airway pressure (CPAP) in patients with CHF and COSA [3][4][5]. In our opinion, some aspects of the report by ARZT et al [1] need to be underlined and discussed because of their potential daily clinical implications as well as the design of future studies.…”
mentioning
confidence: 94%
“…We read with great interest the recent report by ARZT et al [1]. They investigated the potential benefit of auto-servoventilation (ASV) in addition to an optimal medical management (OMM) on cardiac function and quality of life in patients with congestive heart failure (CHF) coexisting with central and obstructive sleep apnoea (COSA).…”
mentioning
confidence: 99%
See 1 more Smart Citation